Index Based Assessment of Factors Affecting Farm Diversification in Haryana - Jose, Elizabeth; K. Ponnusamy; M.L .Kamboj (Indian Journal of Extension Education, 2023)
The study aimed to assess the factors affecting farm diversification was conducted in Kaithal, Hisar, and Bhiwani districts of Haryana in 2021 by selecting 180 farmers and 60 experts. The factors influencing farm diversification were assessed through the index method, Garret ranking, and RBQ method. The proximity of the National Capital Region (NCR), increased road density, and improved access to market information were found to favour the diversification of farm enterprises whereas, market uncertainties and climate induced factors were perceived to hinder it. Farmers did not show interest in Kharif crops such as maize , sorghum, pearl millet, and cotton in the study area, mainly because of non-availability of labour at an affordable rate for manual harvesting. The findings act as supporting evidence of the factors that are beneficial for achieving sustainability in the future farming sector of Haryana.